Seasonal Variation in Photosynthesis, Transpiration and Stomatal Conductance in Promising Genotypes of Leucaena leucocephala - Mishra, Seema; Bhatt, R. K. (Indian Journal of Agroforestry, 2020)
Five promising genotypes of Leucaena leucocephala (viz., S24, S22, S14, S10 and K8) were studied for their seasonal variations in physiological characteristics under natural condition in semi-arid tropics. Rate of photosynthesis (PN), and stomatal conductance (gs) of all the genotypes were higher during July to November which declined in winter months and reached minimum in the month of June. Selection S24 showed maximum rate of PN and gs followed by S10 while other genotypes were at par. Transpiration rate (E) was higher in S14 and K8 during July- October while lowest transpiration rate was in S24 in the months of May -June. The lowest rate of water loss during the process of transpiration in S24 exhibits its economical water use for sustainability of growth in hot summer. PN /E ratio was highest in the month of December-January in all the genotypes predicting their highest water use efficiency in the process of CO2 assimilation during this period. The carboxylation efficiency was highest in rainy season and lowest in summer in-.all the genotypes and maximum values were recorded in S24. S24 had maximum rate of photosynthesis, stomatal conductance, water use efficiency, caboxylation efficiency and minimum rate of transpiration which indicates its superiority over other genotypes and may be selected as fast growing and higher biomass producing genotypes for semi-arid tropical region.